2007
DOI: 10.1088/0022-3727/40/15/049
|View full text |Cite
|
Sign up to set email alerts
|

Growth of p-type ZnO thin films by (N, Ga) co-doping using DMHy dopant

Abstract: We investigate p-type doping in ZnO prepared by metal-organic chemical vapour deposition with dimethylhydrazine (DMHy) as the nitrogen dopant source. Results obtained by x-ray photoelectron spectroscopy show that DMHy exhibits a narrow temperature window from 500 to 550 °C for efficient nitrogen incorporation and that nitrogen doping is critically influenced by growth conditions, e.g. the N/Ga flux ratio in growth. Within an appropriate N/Ga flux ratio range, p-type ZnO can be realized. The effect of the N/Ga … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The emission peak at 3.312 eV can be attributed to the conduction band to acceptor transition (or free electrons to the acceptor (FA) transition) as reported in In-P codoped ZnO [36]. However, the peak at 3.235 and 3.163 eV is assigned to donor-acceptor pair (DAP) transition and its longitudinal optical (LO) phonon replicas of DAP-LO with a periodic spacing of $72 meV, respectively, which is identical with the results for GaN codoped p-type ZnO [37]. Moreover, DAP emission is observed at 3.238 eV for p-type Ndoped ZnO [38].…”
Section: Resultssupporting
confidence: 81%
“…The emission peak at 3.312 eV can be attributed to the conduction band to acceptor transition (or free electrons to the acceptor (FA) transition) as reported in In-P codoped ZnO [36]. However, the peak at 3.235 and 3.163 eV is assigned to donor-acceptor pair (DAP) transition and its longitudinal optical (LO) phonon replicas of DAP-LO with a periodic spacing of $72 meV, respectively, which is identical with the results for GaN codoped p-type ZnO [37]. Moreover, DAP emission is observed at 3.238 eV for p-type Ndoped ZnO [38].…”
Section: Resultssupporting
confidence: 81%
“…28 However, the peak at 3.241 eV and 3.168 eV are assigned to donor-acceptor pair (DAP) transition and its longitudinal optical (LO) phonon replicas of DAP-LO with a periodic spacing of $72 meV, respectively. 29 Based on the literature reported previously, 30 the 3.310 and 3.241 eV peaks are often observed in N-doped ZnO with good p-type conductivity, and assigned to emissions of free electrons to N-related acceptors as well as a native donor and an N-related acceptor pair (DAP), respectively. Therefore, it is deduced that the N-related acceptor in ZnO:(P, N) film may be arise from an complex acceptor formed by (P, N) dual acceptor doping, the p-type conduction of the ZnO:(P, N) film comes from contribution of the complex acceptor.…”
Section: Resultsmentioning
confidence: 80%
“…It is proved that choosing appropriate acceptor dopant and doping method is very important in the preparation of p-type ZnO. Therefore, many attempts have been made, both experimentally and theoretically, to obtain p-type ZnO thin films by single doping of I or V group elements and codoping of III-V groups [5][6][7][8][9][10][11][12][13][14]. The theoretical studies demonstrated the group I elements when incorporated on Zn site, such as Li Zn , might be better p-type dopants than group V elements for introducing shallowness of acceptor levels [15].…”
Section: Introductionmentioning
confidence: 99%